The effect of plasmin on age gelation in UHT milk - Bekker, Aninke (University of the Free State, 2019)
Abstract not available
Thesis (Ph.D. (Consumer Science))--University of the Free State, 2019
Keywords: Plasmin; Ultra-high temperature milk; Milk - Treatments; Age gelation; Dairy industry